Effect of marine incursion on the formation of lacustrine source rocks: A case study of mudstones from the third member of the Shahejie Formation in the southwestern Bozhong Sag, Bohai Bay Basin, China - Qian Huang; Yaohui Xu; Feilong Wang; Haifeng Yang; Ning Wang; Jiaohao He (Journal of Natural Gas Geoscience, 2023)
Bozhong Sag, the largest hydrocarbon generation sag in the Bohai Bay Basin, is characterized by presence of the third member of the Shahejie Formation (E2s3), which serves as a significant source rock. While previous studies have provided insights into the source material, sedimentary environment, and thermal maturity of the E2s3 source rocks, further investigation is required to deepen our understanding of sedimentary events and biological sources. In this research, nine mudstone core samples from the southwestern Bozhong Sag were thoroughly analyzed using organic-inorganic geochemistry and organic petrology. The results reveal the following key findings: (1) The middle and lower sections of the third member of the Shahejie Formation are characterized by high-quality source rocks, with the lower section exhibiting superior quality. The increase in water salinity during warm and humid climates, and the detection of 24-n-propylcholestane compounds reflected the occurrence of transgression events in the E2s3. These transgressions gradually increased from the lower sections to the middle sections of the E2s3. (2) The studied samples exhibit abundant presence of 4α-methyl-24-ethylcholestanes, 24-n-propylcholestanes, 2α-methylhopanes, oleananeabundant algainite, and a small amount of vitrinite. This diversity of hydrocarbon-forming organisms in the E2s3 source rocks is evident. (3) The moderate marine incursion in the lower part of the E2s3 results in nutrient elements that promote the flourishing of bacteria and algae, providing an abundant material basis for the formation of high-quality source rocks. However, the large-scale marine incursion in the middle of the E2s3 weakens water eutrophication, resulting in a decrease in the quality of source rocks compared to the lower part of the E2s3.